Enhancing precision in cancer treatment: the role of gene therapy and immune modulation in oncology - Youssef, Emile; Fletcher, Brandon; Palmer, Dannelle (Frontiers in Medicine, 2025)
Gene therapy has long been a cornerstone in the treatment of rare diseases and genetic disorders, offering targeted solutions to conditions once considered untreatable. As the field advances, its transformative potential is now expanding into oncology, where personalized therapies address the genetic and immune-related complexities of cancer. This review highlights innovative therapeutic strategies, including gene replacement, gene silencing, oncolytic virotherapy, CAR-T cell therapy, and CRISPR-Cas9 gene editing, with a focus on their application in both hematologic malignancies and solid tumors. CRISPR-Cas9, a revolutionary tool in precision medicine, enables precise editing of cancer-driving mutations, enhancing immune responses and disrupting tumor growth mechanisms. Additionally, emerging approaches target ferroptosis—a regulated, iron-dependent form of cell death—offering new possibilities for selectively inducing tumor cell death in resistant cancers. Despite significant breakthroughs, challenges such as tumor heterogeneity, immune evasion, and the immunosuppressive tumor microenvironment (TME) remain. To overcome these barriers, novel approaches like dual-targeting, armored CAR-T cells, and combination therapies with immune checkpoint inhibitors and ferroptosis inducers are being explored. Additionally, the rise of allogeneic “off-the-shelf” CAR-T therapies offers scalable and more accessible treatment options. The regulatory landscape is evolving to accommodate these advancements, with frameworks like RMAT (Regenerative Medicine Advanced Therapy) in the U.S. and ATMP (Advanced Therapy Medicinal Products) in Europe fast-tracking the approval of gene therapies. However, ethical considerations surrounding CRISPR-based gene editing—such as off-target effects, germline editing, and ensuring equitable access—remain at the forefront, requiring ongoing ethical oversight. Advances in non-viral delivery systems, such as lipid nanoparticles (LNPs) and exosomes, are improving the safety and efficacy of gene therapies. By integrating these innovations with combination therapies and addressing regulatory and ethical concerns, gene therapy is poised to revolutionize cancer treatment, providing durable, effective, and personalized solutions for both hematologic and solid tumors.